1996
DOI: 10.1002/masy.19961110106
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic chain transfer polymerisation (cctp) of methyl methacrylate: Effect of catalyst structure and reaction conditions on chain transfer coefficient

Abstract: Catalytic chain transfer polymerisation of methyl methacrylate has been investigated by a range of cobalt(I1) complexes. The effect of catalyst structure, reaction temperature and solvent has been examined. At 60°C in the absence of solvent, the chain transfer coefficient, Cs, for MMA and cobaloximes modified by bridging BF2 groups e.g. 3 is found to be 40,900, this is constant over a wide mass range. Cs is lowered when catalysts of larger cross sectional area are used supporting a diffusion controlled process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(81 citation statements)
references
References 8 publications
3
78
0
Order By: Relevance
“…The styrene radicals are about 20 times more reactive than the methacrylate radicals towards thiols. [3] In contrast, the methacrylate radicals are about 20 times more reactive towards COPhBF [14,22] (assuming that the HEMA and MMA radicals have a similar reactivity in chain transfer reactions). Consequently, significant composition drift, leading to different ratios of the propagating radicals, would result in a large drift in the molecular weight distributions.…”
Section: Composition Driftmentioning
confidence: 99%
“…The styrene radicals are about 20 times more reactive than the methacrylate radicals towards thiols. [3] In contrast, the methacrylate radicals are about 20 times more reactive towards COPhBF [14,22] (assuming that the HEMA and MMA radicals have a similar reactivity in chain transfer reactions). Consequently, significant composition drift, leading to different ratios of the propagating radicals, would result in a large drift in the molecular weight distributions.…”
Section: Composition Driftmentioning
confidence: 99%
“…This has been suggested by several authors. [8,13,14] Heuts et al [17][18][19] elaborated on this topic and found evidence that supported the hypothesis that the transfer reaction in catalytic chain transfer of methacrylates is indeed diffusion controlled. These conclusions were based on trends in C T for a series of methacrylates [17,19] and on enhanced catalyst activity when polymerizations are run in supercritical CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The values in solution are generally lower than those in bulk. [12][13][14] In earlier literature this decrease was claimed to be caused by so-called solvent effects: interactions of solvent molecules with the active catalytic center. From studies in emulsion polymerization [15] and studies of the polymerization of methacrylic acid, [16] it is known that CoBF decomposes slowly in the presence of acids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can, in principle, be accomplished by diluting the monomer solution to varying extents. However, significant solvent effects can occur in the current system, as a solvent molecule may act as the axial ligand for the Co(II) complex and may significantly alter the electronic properties of the catalyst 7) . The latter effect may lead to a different reactivity of the catalyst and hence the experiment may not be suitable for testing our predictions.…”
Section: Derivation Of Kinetic Expressionsmentioning
confidence: 99%